Exosome-Derived Noncoding RNAs as a Promising Treatment of Bone Regeneration - Bei Yin; Qingge Ma; Chenghao Song; Lingyi Zhao; Fanyuan Yu; Chenglin Wang; Yu Shi; Ling Ye (Hindawi Limited, 2021)
The reconstruction of large bone defects remains a crucial challenge in orthopedic surgery. The current treatments including autologous and allogenic bone grafting and bioactive materials have their respective drawbacks. While mesenchymal stem cell (MSC) therapy may address these limitations, growing researches have demonstrated that the effectiveness of MSC therapy depends on paracrine factors, particularly exosomes. This aroused great focus on the exosome-based cell-free therapy in the treatment of bone defects. Exosomes can transfer various cargoes, and noncoding RNAs are the most widely studied cargo through which exosomes exert their ability of osteoinduction. Here, we review the research status of the exosome-derived noncoding RNAs in bone regeneration, the potential application of exosomes, and the existing challenges.